2021
DOI: 10.3390/d13080366
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Culture-Dependent Gram-Negative Rhizobacteria Associated with Manihot esculenta Crantz Plants Subjected to Water-Deficit Stress

Abstract: There is a lack of studies on the root-associated bacterial microbiome of cassava plants. The identification and characterization of rhizobacteria can contribute to understanding the adaptation of the agriculturally important crop plants to abiotic stress. Rhizobacteria play a significant role in plants, as they can alleviate the drought stress by various mechanisms that enhance the plant growth under these stressor conditions. In this study, Gram-negative bacterial strains from the plant rhizosphere of cassav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Drought is defined as a state of the total water capacity being within the range of 12-20% for a period of 16 days and can be distinguished from the water deficit, which is the state of water capacity falling below 30% [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Drought is defined as a state of the total water capacity being within the range of 12-20% for a period of 16 days and can be distinguished from the water deficit, which is the state of water capacity falling below 30% [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to be able to produce PGPR commercially in the future. For this reason, business management and quality testing are needed [11,12,13].…”
Section: Figure 5 Pgpr Application Demonstration On Cassava Plants In...mentioning
confidence: 99%
“…Research results from Ilyas (2020) showed that giving mycorrhizal inoculums to Renek's cassava plants can increase the tuber yield of cassava by 5.18 tons/ha compared to Renek's cassava plants that are not given mycorrhizal inoculums of 1.68 tons/ha [4,13,14]. While the Keratan system on cassava seeds can increase root proliferation so that cassava yields reach 51 tons/ha [5,11,12,1]. Withdrawing cassava seedling stems and mycorrhizal inoculation, cassava yields increased by 54% (54.32 tons/Ha) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in recent years, the identification and characterization of rhizobacteria in agricultural production is considered to be of great significance. In our Special Issue, Zapata et al [12] isolated 58 rhizobacterial strains from the plant rhizosphere of cassava Manihot esculenta Crantz CIAT MCOL1734 variety subjected to water deprivation, and identified the bacteria belonged to 12 genera: Achromobacter, Acinetobacter, Aeromonas, Buttiauxella, Cronobacter, Klebsiella, Ochrobactrum, Pluralibacter, Pseudomonas, Rhizobium, Serratia, and Sphingomonas. The cassava roots constitute a great reservoir of potential Gram-negative rhizobacteria with remarkable biotechnological applications.…”
mentioning
confidence: 99%